2019
DOI: 10.3390/ma12152439
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Dependence of Poisson’s Ratio on Liquid Fragility and Atomic Packing Density in Oxide Glasses

Abstract: Poisson’s ratio (ν) defines a material’s propensity to laterally expand upon compression, or laterally shrink upon tension for non-auxetic materials. This fundamental metric has traditionally, in some fields, been assumed to be a material-independent constant, but it is clear that it varies with composition across glasses, ceramics, metals, and polymers. The intrinsically elastic metric has also been suggested to control a range of properties, even beyond the linear-elastic regime. Notably, metallic glasses sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 162 publications
(200 reference statements)
4
27
0
Order By: Relevance
“…Strongly interconnected glass networks with low atomic packing density often exhibit lower Poisson's ratio as compared to more densely packed glasses with a lower degree of cross-linking. 29 Although the universal validity of these simplistic correlations has very recently been questioned, 59 the atomic packing density and network dimensionality have frequently been utilized as useful metrics to describe compositional variations in Poisson's ratio for a variety of silicate 48,[60][61][62][63][64] and aluminosilicate glasses. [65][66][67] The observed increase of with increasing molar ratio R may originate from the parallel increase of C g upon progressive substitution of Na 2 O by K 2 O.…”
Section: Properties Of Bulk Reference Glassesmentioning
confidence: 99%
“…Strongly interconnected glass networks with low atomic packing density often exhibit lower Poisson's ratio as compared to more densely packed glasses with a lower degree of cross-linking. 29 Although the universal validity of these simplistic correlations has very recently been questioned, 59 the atomic packing density and network dimensionality have frequently been utilized as useful metrics to describe compositional variations in Poisson's ratio for a variety of silicate 48,[60][61][62][63][64] and aluminosilicate glasses. [65][66][67] The observed increase of with increasing molar ratio R may originate from the parallel increase of C g upon progressive substitution of Na 2 O by K 2 O.…”
Section: Properties Of Bulk Reference Glassesmentioning
confidence: 99%
“…Under the same load, glasses with higher fracture toughness can exhibit stronger resistance to crack growth, and this results in the decrease of crack length. Notably, the fracture toughness of R = La, Sm, and Gd glass is 1.21 MPa$m 0.5 , 1.39 MPa$m 0.5 , and 1.52 MPa$m 0.5 , respectively, which is much larger than the values of current commercially available oxide glasses, such as silicates, borates, borosilicate, etc., which is reported to be lower than 1 MPa$m 0.5 (Quinna and Swab, 2013;To, 2019;Østergaard et al, 2019;Rouxel and Yoshida, 2017;Yao, 2016;Scannell et al, 2017;Vullo and Davis, 2004;Wiederhorn et al, 1974;Mezeix, 2017;Kato et al, 2010;Reddy et al, 1988), as shown in Figure 5C (areas below the gray short dash line). Currently, the highest fracture toughness of oxide glasses is reported to be 1.36 MPa m 0.5 using the single-edge pre-cracked beam method (To et al, 2021).…”
Section: Indentation Fracture Toughnessmentioning
confidence: 85%
“…In the present work, following [13], fragility is calculated through density dependence, at ζ = ζ g . Correlation between the Poisson's ratio and fragility was found [32,37,[45][46][47][48][49][50]65] to be non-universal even within only molecular systems. Thus, while there exist a fundamental link between fragility and elasticity through the basic interaction potential, and the underlying structure of the liquid influences its long time dynamics, and the observed correlation between m and ν demonstrated in the present work is still at the level of a hypothesis.…”
Section: Discussionmentioning
confidence: 99%